2017
DOI: 10.1038/cdd.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminases factor XIII-A and TG2 regulate resorption, adipogenesis and plasma fibronectin homeostasis in bone and bone marrow

Abstract: Appropriate bone mass is maintained by bone-forming osteoblast and bone-resorbing osteoclasts. Mesenchymal stem cell (MSC) lineage cells control osteoclastogenesis via expression of RANKL and OPG (receptor activator of nuclear factor κB ligand and osteoprotegerin), which promote and inhibit bone resorption, respectively. Protein crosslinking enzymes transglutaminase 2 (TG2) and Factor XIII-A (FXIII-A) have been linked to activity of myeloid and MSC lineage cells; however, in vivo evidence has been lacking to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 60 publications
6
48
1
Order By: Relevance
“…The increased osteoclastogenesis was also seen in double FXIII‐A/TG2 deficient monocytes in vitro demonstrating that the two enzymes negatively regulate osteoclastogenesis. However, similarly, as in the work of Raghu et al () a chemical inhibitor of TGs blocked osteoclastogenesis in our study, which was attributed to expression of TG1 in wild type and FXIII‐A/TG2 deficient monocytes and osteoclasts (Mousa et al, ). Although we did not see a bone phenotype in either, individual TG2 or FXIII‐A knockouts (Mousa et al, ), Kim et al () showed recently that TG2 deficient mice exhibited increased osteoclast number and lower trabecular bone mass in vivo and that siRNA knockdown of TG2 gave rise to increased osteoclastogenesis in vitro (Kim et al, ).…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…The increased osteoclastogenesis was also seen in double FXIII‐A/TG2 deficient monocytes in vitro demonstrating that the two enzymes negatively regulate osteoclastogenesis. However, similarly, as in the work of Raghu et al () a chemical inhibitor of TGs blocked osteoclastogenesis in our study, which was attributed to expression of TG1 in wild type and FXIII‐A/TG2 deficient monocytes and osteoclasts (Mousa et al, ). Although we did not see a bone phenotype in either, individual TG2 or FXIII‐A knockouts (Mousa et al, ), Kim et al () showed recently that TG2 deficient mice exhibited increased osteoclast number and lower trabecular bone mass in vivo and that siRNA knockdown of TG2 gave rise to increased osteoclastogenesis in vitro (Kim et al, ).…”
Section: Introductionsupporting
confidence: 90%
“…Previous studies, including ours, have linked TG enzymes and their activity to monocyte, macrophage, and osteoclast function in vitro and in vivo (Adany et al, ; Akimov & Belkin, ; Bagoly et al, ; Chrobok et al, ; Kim et al, ; Mousa et al, ; Raghu et al, ) and our recent work demonstrated the relevance of TG2, FXIII‐A in regulation of osteoclastogenesis in mice as well as showed for the first time the presence of TG1 in osteoclasts (Mousa et al, ). In the present study, we have continued the exploration on the role of TGs in osteoclastogenesis and show that TG inhibitors are highly potent blockers of osteoclast differentiation, fusion and migration.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The phenotype of all 3 independent global TG2 knockout lines is normal at baseline, suggesting a negligible developmental role for TG2. Indeed, double-FXIII-A/TG2 knockout mice exhibit only a transient delay in bone mineral density and growth relative to wild-type mice (68), and double-TG1/ TG2 knockout mice show epidermal features similar to TG1 knockout mice (69). Most studies are thus focusing on the pathologic role of TG2 function.…”
Section: Ongoing Researchmentioning
confidence: 99%
“…Finally, it is clear that many biologic functions of FXIII have not been thoroughly elucidated. In addition to coagulation, FXIII may have roles in arthritis(50), adipogenesis(51), and cardiac repair(52, 53). It will be important to understand the impact of FXIII inhibition on these situations before the benefit of a FXIIIa antagonist can be realized in the clinic.…”
Section: Discussionmentioning
confidence: 99%